2016
DOI: 10.1016/j.biombioe.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle greenhouse gas emissions analysis of catalysts for hydrotreating of fast pyrolysis bio-oil

Abstract: Bio-oil from fast pyrolysis of biomass requires multi-stage catalytic hydroprocessing to produce hydrocarbon drop-in fuels. One process design currently in development involves fixed beds of ruthenium-based catalyst and conventional petroleum hydrotreating catalyst. As the catalyst is spent over time as a result of coking and other deactivation mechanisms, it must be changed out and replaced with fresh catalyst. A main focus of bio-oil upgrading research is increasing catalyst lifetimes to 1 year. Biofuel life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…From cradle-to-gate, platinum production GHG emissions are 113 kgCO2e/kg [17]. This result agrees with the outcome presented by Snowden-Swan et al [10], who, using different data from that which we used in our analysis, reported a nearly identical GHG intensities for platinum production in South Africa of 112 kgCO2e/kg. Platinum production GHG emissions are high because the 72% of the energy input to the energy-intensive process is electricity, which is produced largely from coal.…”
Section: Figure 1 Pt /Alumina-supported Catalyst Supply Chainsupporting
confidence: 92%
See 2 more Smart Citations
“…From cradle-to-gate, platinum production GHG emissions are 113 kgCO2e/kg [17]. This result agrees with the outcome presented by Snowden-Swan et al [10], who, using different data from that which we used in our analysis, reported a nearly identical GHG intensities for platinum production in South Africa of 112 kgCO2e/kg. Platinum production GHG emissions are high because the 72% of the energy input to the energy-intensive process is electricity, which is produced largely from coal.…”
Section: Figure 1 Pt /Alumina-supported Catalyst Supply Chainsupporting
confidence: 92%
“…Although several studies have presented advances in catalytic technologies for the transformation of biomass into biofuels [7, 8, and 9], to our knowledge, very few studies have discussed the environmental impact of catalyst use in biofuel production. For instance, Snowden-Swan et al [10], presented a life-cycle analysis (cradle-to-gate) of two catalysts' (NiMo/Al2O3 and Ru/C) production and the environmental impact of using these catalysts in the hydrotreating of fast pyrolysis bio-oil. They estimated that the contribution of catalyst consumption to conversion stage GHG emissions can vary between 0.5% and 5% depending on the co-product treatment method applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni and zeolite instead of manufactured catalysts). Very limited research has compared the environmental profiles of catalysts for hydrotreating fast pyrolysis oils [748]. Snowden-Swan et al…”
Section: Catalysts and Conversion Technologiesmentioning
confidence: 99%
“…The remaining CO 2 produced from off-gas combustion is biogenic. The life cycle inventory of the catalyst utilized for the catalytic upgrade was not accounted for in this study because previous studies have shown that the life cycle inventory of the catalyst has little effect on the overall life cycle emission of the pathway. …”
Section: Methodsmentioning
confidence: 99%